Особливості аерофітних водоростей та фотобіонтів лишайників, пов'язані з їх пристосуванням до життя в наземних умовах - Михаилюк, Т.І.; Дарієнко, Т.М.; Шнюкова, Є.І.; Кондратюк, С.Я. (Український фітоценологічний збірник, 2006)
Пополнены данные о видовом составе и экологии аэрофитных водорослей и водорос-лей-фотобионтов лишайников в результате исследования этой малоизвестной группы споро-вых растений в различных местообитаниях Украины. Аэрофитные водоросли представлены не-большим количеством видов, которые приспособлены к жизни в наземных условиях. Выявлена специфика видового состава некоторых групп аэрофитных водорослей — эпифитов, литофи-лов, лишайниковых фотобионтов. Проанализированы особенности распространения аэрофитных водорослей на различных субстратах. Изучены различные группы углеводов в клетках наиболее обычных видов аэрофитных водорослей. As a result of investigation of various habitats of aerophytic and lichen algae of Ukraine, the data about species composition and ecology of this little known group of sporen plants were enriched. It is known, that aerophytic algae are represented by the small number of species, which are adapted to the life in terrestrial conditions. Specific species composition of some groups of aerophytic algae— epiphytic, lithophilic, lichen photobionts, was found. The peculiarities of distribution of aerophytic algae on various substrates are analysed. Various groups of carbohydrates in cells of most common species of aerophytic algae are analysed.